The role of Husband Support in The Success of Early Initiation of Breastfeeding (EIBF) in Health Care Facilities. - Masnila, Masnila; Siregar, Nurlama; Tarigan, Siang br (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the role of husband support in the success of Early Initiation of Breastfeeding (EIBF) implementation in health facilities. EIBF is a crucial step in improving the health and survival of newborns, yet its implementation is often hindered by the lack of family involvement, particularly the husband. This research uses a quantitative approach with a cross-sectional design and involves 100 postpartum mothers who gave birth in various types of health facilities. Data were collected through a closed-ended questionnaire and analyzed using the Chi-Square test and logistic regression. The results showed that husband support, especially in the form of emotional and informational support, had a significant relationship with the success of EIBF. Mothers who received high support from their husbands were twice as likely to successfully implement EIBF compared to those who did not receive such support. The conclusion of this study emphasizes the importance of involving husbands in education programs and maternal care policies. Health facilities also need to implement a more inclusive and family-friendly service approach to sustainably improve EIBF practices.